Epidemiology of Colorectal Adenomas and Histopathological Assessment of Endoscopic Specimens in the Colorectum - Munding, Johanna (Viszeralmedizin, 2014)
BACKGROUND: Colorectal cancer is one of the most frequently observed neoplasms in the world. It develops from intraepithelial neoplasia of the colorectal mucosa, and these precursor lesions are also known as adenoma. As the precursor lesion is known and can be detected easily, efficient screening strategies are available for a reliable prevention of colorectal adenocarcinoma, e.g. by colonoscopy. METHODS: Literature databases (PubMed) were searched selectively for the keywords ‘colorectal adenoma’, ‘epidemiology’, and ‘resection techniques’. The results are presented in the following text, also taking into account our own experience and the current S3 guidelines. RESULTS: Endoscopic resection samples are one of the specimens most frequently assessed by pathologists. Therefore, gastroenterologists expect standardized and well-structured pathology reports, stating relevant information concerning the removed lesions and recommendations for clinical management. These aspects are summarized in the evidence-based S3 guideline. CONCLUSION: As a consequence of colorectal adenoma resection during screening procedures, the carcinoma incidence is decreasing. For further advancements in successful prevention, knowledge of different precursor lesions (conventional adenoma, serrated adenoma) is important, but also structured communication between the different disciplines engaged in colorectal cancer screening.